RAGAM DIEKSIS DALAM CERITA RAKYAT SIMALIN DEMAN: KAJIAN PRAGMATIK - Sianipar, Vina Merina Br; Carolina, Carolina (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
Existing research is part of a structural form of speech that will be adapted to communication aimed directly at events. Dieksi is a phenomenal part of linguistics with the aim of providing expressions of meaning in the context. The aim of the research is to describe the types of dieksis from the data by means of descriptions found in the Simalem Deman folklore. The focus of this research is to identify variations in existence so that the amount of data that is dominant in literary works is known. Furthermore, the method used is descriptive qualitative with reading and note-taking techniques. Based on research on various types of diexis, personal deixis was found with a total of 599 data, place deixis with a total of 43 data, time deixis with a total of 25 data found, discourse diexis found with a total of 146, and then social deixis with a total of 432 data.